Impact of Green Innovation towards economic performance of food industrial firms applying green industry approach under green industry project of Ministry of Industry Thailand - Tantayanubutr, Monika; Panjakajornsak, Vinai (My University, 2017)
This research aims to develop a structural model to analyze the impact of Green Innovation towards the economic performance of food industrial firms implementing Green Innovation approach, in compliance with the national Green Industry initiative in Thailand. The conceptual framework is built on the study of relevant variables from existing theories and empirical research findings, focusing on the correlation of Green Supply Chain Integration and Corporate Social Responsibility. The target population is selected from entrepreneurs and Chief Executive Officers involved in food industry, of those 2,145 accredited Green Industry Mark from the Ministry of Industry Thailand. Research methodology applies the combination of collecting quantitative data from questionnaires, and exploring qualitative data from in-depth interviews to reaffirm the findings. An analysis on inferential statistics is to be conducted through Structural Equation Modeling. The research results will address key factors and formulate a structural model that provides new insight in analyzing Green Innovation challenges that impact economic performance of food industry in Thailand.
Keywords: Corporate Social Responsibility; Economic Performance; Food Industry; Green Industry; Green Innovation; Green Supply Chain Integration